2017
DOI: 10.1021/acs.jafc.7b00233
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated mTOR Signaling and Enhanced Glucose Homeostasis by Dietary Supplementation with Lotus Seedpod Oligomeric Procyanidins in Streptozotocin (STZ)-Induced Diabetic Mice

Abstract: This study investigated the protective role of lotus seedpod oligomeric procyanidins (LSOPC) and synbiotics (Bifidobacterium Bb-12 and xylo-oligosaccharide) against high fat and streptozotocin (STZ)-induced diabetes. Administration of LSOPC or synbiotics had no effect on blood glucose in normal mice. Treatments with LSOPC for 12 weeks markedly reduced blood glucose, FFA, endotoxin, and GHbA1c and improved glucose homeostasis, lipid metabolism, and insulin levels. In addition, administration of LSOPC significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 66 publications
0
37
0
Order By: Relevance
“…This plant-based bioactive agent has previously been shown to exhibit a variety of beneficial health effects. In vivo and in vitro studies have demonstrated that it has hypolipidemia, hypoglycemic activity, and the ability to inhibit cognitive impairment [6][7][8][9]. Furthermore, Duan et al [10] reported that procyanidins from lotus had significant growth inhibition effects on mouse melanoma B16 both in vivo (inhibiting tumor growth in C57BL/6 J mice by 55.3% in terms of average tumor weight) and in vitro (possessing cytotoxicity against mouse melanoma B16 cell line).…”
Section: Introductionmentioning
confidence: 99%
“…This plant-based bioactive agent has previously been shown to exhibit a variety of beneficial health effects. In vivo and in vitro studies have demonstrated that it has hypolipidemia, hypoglycemic activity, and the ability to inhibit cognitive impairment [6][7][8][9]. Furthermore, Duan et al [10] reported that procyanidins from lotus had significant growth inhibition effects on mouse melanoma B16 both in vivo (inhibiting tumor growth in C57BL/6 J mice by 55.3% in terms of average tumor weight) and in vitro (possessing cytotoxicity against mouse melanoma B16 cell line).…”
Section: Introductionmentioning
confidence: 99%
“…LLSPCs have far‐ranging pharmacological actions. LSPCs may restrain oxidative stress injury , reverse hippocampal neuronal cell death induced by extremely low‐frequency electromagnetic fields exposure in mice , modulate glucose disposal in peripheral target tissues of streptozotocin‐induced diabetic mice , defend against nonalcoholic fatty liver disease in Sprague‐Dawley male rats , prohibit the formation of advanced glycation end product, has a powerful whole body radioprotective activity , and ameliorative cognitive deficits in aged impaired animals . In the present study, LSPC treatment reduced walking time and forelimb lifting‐up frequency, cerebral levels ADMA, noradrenaline, and glutamic acid; augmented total sleep time, cerebral 5‐hydroxytryptamine concentration, and cerebral γ‐aminobutyric acid concentration concomitantly with elevated cerebral expressions of DDAH‐1, DDAH2, and nNOS in insomniac rats.…”
Section: Discussionmentioning
confidence: 99%
“…In order to establish insomniac rat models, p‐chlorophenylalanine (300 mg/kg body weight) were intraperitoneally injected into the rats in the morning of each day for two consecutive days. LSPC was dissolved in physiological saline as described previously . Normal rat and untreated insomniac rat were treated with vehicle of LSPC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that lotus seedpod is rich in polyphenols and an important natural source of oligomers and polymers of catechin, which are also denominated procyanidins [19,20]. In recent years, procyanidins from lotus seedpod have been shown to possess antioxidant, anti-aging, anti-memory impairment, radioprotective, anti-glycative, and anti-inflammatory activities [20][21][22][23][24][25]. However, little information is available on the anti-lipid accumulation and anti-lipotoxic effect of lotus seedpod extract (LSE) in hepatocytes.…”
Section: Introductionmentioning
confidence: 99%